An historical overview of flexible learning in New Zealand from 1990 to the present - Don Bewley (Flexible Learning Association of New Zealand, 2012)
The recent progress in New Zealand of flexible learning is reviewed, together with its underlying concepts as expounded at the 1995 DEANZ conference by Bruce King, an Australian. These concepts, which already are known and were developed in New Zealand during the 1990s, are considered in the context of changes in New Zealand's political policies for education. The implementation of flexible learning in that environment is traced, particularly in post-secondary institutions engaged in distance learning.